MODERN LEADERSHIP AND IMPACT ON GOOD GOVERNANCE - Veronica A. BUTNARU; Svetlana I. COJOCARU; Tatiana M. Tofan (Management Intercultural, 2013)
This article proposes a new model for understanding leadership in the public sector. Public sector leadership should respond to the real and daunting challenges facing governments and enhance their capacity to deal with them. The key factor here is to differentiate between leading and managing. Leaders in the public service need to be constantly reminded of the need to go beyond management. Leadership is an important and crucial variable that leads to enhanced management capacity, as well as organisational performance. Leadership in public sector is accepted to be an important component of good governance in general and good public governance in particular. In this context, this article will present recent developments in leadership literature with a view to highlight significance of public leadership while also providing food for thought for public leadership in the Republic of Moldova.